Effect of microstructure on the thermal conductivity of disordered carbon - Suarez-Martinez, Irene; Marks, Nigel (American Institute of Physics, 2011)
Computational methods are used to control the degree of structural order in a variety of carbonmaterials containing primarily sp2 bonding. Room-temperature thermal conductivities arecomputed using non-equilibrium molecular dynamics. Our results reproduce experimental data foramorphous and glassy carbons and confirm previously proposed structural models for vitreouscarbons. An atomistic model is developed for highly oriented thin films seen experimentally, with amaximum computed thermal conductivity of 35 W m1 K1. This value is much higher than thatof the amorphous and glassy structures, demonstrating that the microstructure influences thethermal conductivity more strongly than the density.